Relative age effect in professional and youth soccer leagues in Mexico - Fritzler, W. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Youth soccer players are grouped in teams by the same year of birth. The Relative Age Effect (RAE) refers to the more advanced maturity of those children born close to the cutoff date of 1st of January (5), and has been studied in youth soccer in many countries (3). In Mexico, the U15, U17 and U20 youth soccer leagues consist of the same clubs as the First Division. This assumes a similar talent selection process throughout the corresponding leagues. The aim of this study is the comparison of the size and other characteristics of the RAE between Mexicans` youth and First Division teams. Methods: The months of birth, positions and minutes played per game of the Mexican players of the 18 First Division (n=383), U20 (n=417), U17 (n=469), and U15 (n=318) teams were collected from the official Internet site of the Mexican Soccer Federation. The distributions of months in each league were tested for uniformity by the Kolmogorov-Smirnov test (2). The size of the RAE was determined by proportion of births in the first half (4) of the year. Results: All leagues showed a significant RAE (p<0.01), but its size was bigger for the U15 (73.0%) and U17 players (68.9%), while the U20 (57.8%) and the professional players (59.5%) showed smaller sizes. According to player positions, only the U20 and professional goalkeepers, and the professional defenders showed no significant RAE. The sizes of RAE were similar to the sizes of all players, with the exception of the midfielders who presented a bigger size (69%) in the professional league. The correlations between the size of RAE and points obtained in the corresponding league were bigger in U17 (r=0.57) and U15 (r=0.41), and lower in the First Division (r=-0.07) and U20 (r=0.18) teams. The correlation between the months of birth and the minutes played per game was insignificant and only for U17 (r=0.07) above 0.02. Discussion: According to the results of (2), the size of RAE got smaller as the age increased and was correlated with the team level, defined by the game-points obtained. The RAE already disappeared in players with 20 years of age. The main conclusion is that the Mexican soccer clubs should inspect their criteria of talent selection because of favoring the players born early in the year due to their maturity (1), while this bias disappears in the professional and U20 teams, independently of the players` position.